Social Relations in Human and Societal Development
XVI, 253 p.
Keywords: Social interaction is the engine which drives an individual's psychological development and it can create changes on all levels of society. Social Relations in Human and Societal Development includes essays by internationally renowned academics from a range of disciplines including social psychology, international relations and child development.